The Role of the Basic Education Division of the Bengkulu City Education and Culture Office in Character Building for Students (Case Study at SMPN 14 Bengkulu City) - Yozen Fahrozi; Tuti Handayani; Antonio Imanda; Dahlia Dahlia (Social Sciences Journal, 2026)
The research titled “The Role of the Basic Education Division of the Bengkulu City Office of Education and Culture in Student Character Development (A Case Study at SMP Negeri 14 Bengkulu City)” aims to explain the implementation of character development through organizational functions, communication patterns, motivation and social influence, leadership, and organizational culture. This study employs a descriptive qualitative approach using Katz and Kahn’s (1978) theory, which views organizations as open social systems. Data were collected through in-depth interviews, observations, and documentation involving the Basic Education Division of the Bengkulu City Office of Education and Culture as well as SMP Negeri 14 Bengkulu City. The findings show that the Office of Education plays a strategic role in providing guidance, supervision, and policy support to schools. The school acts as the primary implementer in instilling character values through habituation activities such as communal prayer, morning literacy, environmental cleanliness, and religious programs. Communication between the office and the school is effectively established through both formal and informal channels, allowing coordination to run smoothly. Work motivation grows from a shared spirit and a sense of responsibility toward improving educational quality. The leadership style applied is participatory, open to new ideas, and emphasizes role modeling. The organizational culture that emerges reflects values of discipline, responsibility, cooperation, religiosity, and social concern as the foundation for character education. The research findings indicate that character development at SMP Negeri 14 Bengkulu City is effectively implemented due to the alignment between policy formulation and field implementation. The synergy between the Office of Education and the school forms an adaptive, participatory, and character-oriented working system that strengthens students’ values, discipline, and sense of responsibility.